Sprzedaż na rynku europejskim przy wykorzystaniu składu konsygnacyjnego - Szwed, Agata (Sale on European Market with the Consignment Stock Application, 2005)
Export sale with the Consignment Stock application is non-typical kind of transaction between exporter and foreign trade partner. The author indicates characteristic features of such kind of cooperation. The meaning of Consignment Stock in the day of changes on European market is also an object of consideration of this elaboration.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 364-372